Development of Professional Consciousness Students - Zhorakulova Dildora Ziyodullayevna (Genius Journals, 2023)
The formation of professional self-awareness is especially relevant for teachers, psychologists, since the subject of labor acts as an instrument for the implementation of professional functions.
Keywords: Professional self-awareness; motive; cognitive component